Service invocation triggers: a lightweight routing infrastructure for decentralised workflow orchestration. (8th June 2009) - Binder, Walter; Constantinescu, Ion; Faltings, Boi
Traditional, centralised workflow orchestration often leads to inefficient routing of messages. To solve this problem, we present a novel scheme to execute workflows in a fully decentralised way. We introduce service invocation triggers, a lightweight infrastructure that routes messages directly from the producing service to the consuming one, enabling fully decentralised workflow orchestration. An evaluation confirms that decentralised orchestration can significantly reduce the network traffic when compared with centralised orchestration.